2016
DOI: 10.3390/safety2040023
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Depression, and Occupational Injury among Migrant Farmworkers in Nebraska

Abstract: Agriculture is one of the most dangerous industries in the United States. Farmworkers, including migrant farmworkers, are at risk for work-related injuries. This study explores the association between stress, depression, and occupational injury among migrant farmworkers in Nebraska. Occupational injury was hypothesized to significantly increase the odds of farmworkers being stressed and depressed. Two hundred migrant farmworkers (mean age = 33.5 years, standard deviation (SD) = 12.53; 93.0% men, 92.9% of Mexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 28 publications
4
32
0
1
Order By: Relevance
“…In this research, 200 migrant farm workers (mean age 33.5 years, 93% men, 92% Mexican, 59% low education) were interviewed. The results indicate that work-accidents are the triggering factor; in fact, workers with a positive history of trauma report a 7 times higher risk than those without injury [33]. In 2015, Ramos himself sought to identify the main stressors involved in developing depressive symptoms among farmers using the Migrant Farm Worker Stress Inventory (MFWSI).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…In this research, 200 migrant farm workers (mean age 33.5 years, 93% men, 92% Mexican, 59% low education) were interviewed. The results indicate that work-accidents are the triggering factor; in fact, workers with a positive history of trauma report a 7 times higher risk than those without injury [33]. In 2015, Ramos himself sought to identify the main stressors involved in developing depressive symptoms among farmers using the Migrant Farm Worker Stress Inventory (MFWSI).…”
Section: Depression and Anxietymentioning
confidence: 99%
“…Mental health and psychological risk and protective factors for WRIs have been reported in different migrant or expatriate worker populations [ 38 , 39 , 40 ]. A recent review reported that one in four publications on international migrant worker health was in the “mental and psychosocial health” domain [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been associated with health difficulties of migrant workers in France 14 , low-to-medium QOL in rural-to-urban female migrant factory workers in China 15 , and with an impact on social relationships among Burmese domestic female workers in Singapore 16 . Agricultural workers have frequently reported work-related injuries and occupational-health issues related to stress and depression 17,18 . Nearly one third of Cambodian farm workers in eastern Thailand reported occupational injury (back pain/joint pain), and most had limited access to healthcare services 19 , likely compounding the impact on QOL.…”
Section: Introductionmentioning
confidence: 99%